Study of the Influence of Accessibility on Tourist Satisfaction at Mitra Deli Sayum Sabah Natural Baths - Siti Anggiani Syahvira; Lubis, Adelina; Ikbar Pratama (Universitas Kristen Indonesia Toraja, 2024)
This study aims to analyze the effect of accessibility on tourist satisfaction at Mitra Deli Sayum Sabah Natural Baths. The accessibility in question includes factors such as road infrastructure conditions, transportation availability, ease of navigation, and other supporting facilities that affect the comfort and ease of tourists in reaching the location. The research method used is a quantitative approach with data collection techniques through questionnaires distributed to 100 respondents who are tourists visiting the location. The data were analyzed using linear regression to determine the extent to which accessibility affects the level of tourist satisfaction. The results of the study indicate that accessibility has a significant effect on tourist satisfaction, where ease of access contributes greatly to increasing the positive experience of visitors. These findings are expected to be input for managers and local governments to improve the quality of infrastructure and supporting facilities in order to attract more tourists.